Jihadi Rebels in Civil War - Kalyvas, SN (Massachusetts Institute of Technology Press, 2018)
In this essay, I decouple violent jihadism from both religion and terrorism and propose an alternative, nonexclusive understanding of jihadi groups as rebel groups engaged in civil wars. Arguing that jihadi groups can be profitably approached as the current species of revolutionary insurgents, I offer a comparison with an older species, the Marxist rebels of the Cold War. I point to a few significant similarities and differences between these two types of revolutionary rebels and draw some key implications, stressing the great challenges facing jihadi rebels in civil wars.